Localization of Polyribosomes Containing Alkaline Phosphatase Nascent Polypeptides on Membranes of Escherichia coli - Cancedda, Ranieri (1974)
A procedure has been developed for extracting membranes from bacterial cells under conditions that keep a large fraction of bacterial polyribosomes intact. Freeze-thawing spheroplasts in the presence of deoxyribonuclease, followed by differential centrifugation, permits a separation of free and membrane-associated polyribosomes. The latter fraction contains as much as 40% of cell ribosomal ribonucleic acid (RNA) and 55% of cell messenger RNA (mRNA). Nascent polypeptides were divided almost equally between the two fractions, but 70 to 80% of alkaline phosphatase nascent chains, detected both chemically and immunologically, were derived from polyribosomes associated with the bacterial membrane. Analysis of the fractions for mRNA specific for the lac and trp operons by RNA-deoxyribonucleic acid hydridization showed somewhat larger amounts on membrane than on free polyribosomes, but enrichment for nascent alkaline phosphatase (a secreted protein) on membranes was consistently greater, suggesting that polyribosomes making secreted proteins are more tightly bound to membranes. Electron micrographs of the membrane preparations show relatively intact membranes with clusters of polyribosomes on their inner surfaces.